Mobile-Assisted Language Learning through Interaction Applications: Analysis and Evaluation - Eleftheria Alexiadou; Areti-Maria Sougari (Language, Technology, and Social Media)
The rapid advancement of mobile technology has significantly influenced language learning methodologies, giving rise to Mobile-Assisted Language Learning (MALL). This study aims to analyze and classify free texting-based interaction applications for language learning, focusing on their features and pedagogical value. Specifically, the study evaluates and compares two applications, HelloTalk and Linguado, based on a modified framework derived from McMurry et al.’s CALL evaluation methodology and Rosell-Aguilar’s evaluation criteria. Data were collected from twelve Greek adult learners through a combination of judgmental evaluations, participant questionnaires, and follow-up interviews. The findings reveal that HelloTalk demonstrates a greater range of features and user engagement compared to Linguado, with significant strengths in cultural exchange and content enrichment. However, challenges related to user safety and technical functionality were noted in both applications. Additionally, the study explores the theoretical underpinnings of interaction applications, identifying their alignment with constructivism, communicative language teaching, and informal learning frameworks. Practical recommendations are provided to enhance the design and functionality of these tools, emphasizing the integration of advanced features such as chatbots and model conversations. This study contributes to the MALL field by filling gaps in the evaluation and comparison of interaction applications, particularly for adult learners and non-English language contexts. It offers insights into the potential of these tools for fostering communication and intercultural competence, paving the way for future research and practical applications in language education.